Transition From Pediatric to Adult Epilepsy Care: A Difficult Process Marked by Medical and Social Crisis - Camfield, Peter (American Epilepsy Society, 2012)
When epilepsy does not remit in childhood, transition and transfer to adult care is eventually required. Youth must leave the family-centered approach of pediatric care for the individual focus of adult medicine. Evidence from population-based studies indicates that many of those with childhood-onset epilepsy have major social difficulties in adulthood even if their epilepsy has resolved. Epilepsy may have major effects on normal adolescent development, and societal attitudes confound this difficult period in the lives of young people with epilepsy. Very little objective data are available to assist in the designing of models of care for youth with epilepsy; however, based on our clinical experience and the limited available literature, it appears that a transition program to prepare children for adult care is best started during childhood and adolescence. The formal transfer to adult services may be assisted by a transition clinic jointly attended by pediatric and adult epilepsy specialists.